A Cross‐National View on the Organisational Perspective of Writing Centre Work: the Writing Centre Exchange Project (WCEP) - Girgensohn, Katrin; Eriksson, Ann-Marie; O’Sullivan, Íde; Henry, Gina (Journal of Academic Writing, 2020)
This paper gives insights into research conducted within the Writing Centre Exchange Project (WCEP), a research collaboration among three university writing centres in Sweden, Germany and Ireland, which focuses on organisational perspectives on writing centre work. WCEP rests on the theoretical framework of institutional work. Previous research, conducted in US writing centres, developed a model of institutional work in writing centres that includes specific Strategic Action Fields (SAFs) and collaborative learning as a means to interact with stakeholders. By using this model, WCEP has targeted ongoing institutional work intended to establish and sustain missions, goals and activities in and around writing centres. Drawing on participatory action research, WCEP explores the extent to which the institutional work at the three European writing centres correlates with the model. The main findings show that indeed the same strategic action fields are relevant, but furthermore, different subcategories emerge depending on the local context. This paper explores some of the subcategories that differ and draws conclusions for the institutional work of writing centre directors.